Stop that Frog! - Winkler, Henry 1945-; Oliver, Lin; Garrett, Scott (New York, New York, USA : Grosset & Dunlap, an imprint of Penguin Group (USA) LLC, 2014)
When the principal has to be away from school at a conference, Hank's class agrees to take care of the principal's special pet frog, and Hank is chosen to take the frog home for the weekend.
Keywords: Frogs -- Juvenile fiction; Pets -- Juvenile fiction; Responsibility -- Fiction; Schools -- Juvenile fiction; Frogs -- Fiction; Pets -- Fiction; Responsibility -- Fiction; Schools -- Fiction